Gesellschaftsstrukturelle Aspekte von Vulnerabilität gegenüber Naturrisiken - Zehetmair, Swen (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
To date, social vulnerability research has focused primarily on the individual and household levels, and on social institutions relevant to these two benchmarks. In this paper, a widening of the perspective of social vulnerability to natural hazards is proposed to include socio-structural aspects. For a number of reasons, the sociological system theory, which is inextricably linked with the name of Niklas Luhmann, is an obvious choice for this undertaking. Firstly, Luhmann developed a consistent social theoretical definition of risk, which has significantly influenced risk and hazard research in social science. Furthermore, the system theory provides a theory of society that claims to be able to cover all social levels and to describe all social phenomena. The system theory assumes that in modern society social systems are formed of communications. Therefore, in this paper the view is taken that a system-theoretical inspired concept of social vulnerability must also assess communication. First, this paper describes empirical observations about the vulnerability of social systems. This is achieved on the one hand through a categorisation of four forms of social vulnerability. On the other hand, it is based on examples of vulnerability to flood risks in selected social systems. Finally, consideration is given to a system-theoretical concept of social vulnerability that sees the sensitivity of a social system in each of the respective system structures. Vulnerabilities can only be observed for a particular social system, because the configuration of system structures differs from system to system. These fundamental considerations have to be further explored in future work on a consistent social theoretical concept of vulnerability.